Patterns of Responses on Health-Related Quality of Life Questionnaires Among Patients with HIV/AIDS - Kudel, Ian (Blackwell Science Inc, 2006)
BACKGROUND: Health-related quality of life (HRQoL) has become an important facet of HIV/AIDS research. Typically, the unit of analysis is either the total instrument score or subscale score. Developing a typology of responses across various HRQoL measures, however, may advance understating of patients’ perspectives. METHODS: In a multicenter study, we categorized 443 patients’ responses on utility measures (time-tradeoff, standard gamble, and rating scale) and the HIV/AIDS-Targeted Quality of Life (HAT-QoL) scale by using latent profile analysis to empirically derive classes of respondents. We then used linear regressions to identify whether class membership is associated with clinical measures (viral load, CD4, time since diagnosis, highly active antiretroviral therapy [HAART]) and psychosocial function (depressed mood, alcohol use, religious coping). RESULTS: Six classes were identified. Responses across the HAT-QoL subscales tended to fall into 3 groupings—high functioning (Class 1), moderate functioning (Classes 2 and 3), and low functioning (Classes 4 to 6); utility measures further distinguished individuals among classes. Regression analyses comparing those in Class 1 with those in the other 5 found significantly more symptoms of depression, negative religious coping strategies, and lower CD4 counts among subjects in Class 1. Those in Class 5 had been diagnosed with HIV longer, and members of Class 6 reported significantly less alcohol consumption, had higher viral loads, and were more likely to receive HAART. CONCLUSION: Patients with HIV respond differentially to various types of HRQoL measures. Health status and utility measures are thus complementary approaches to measuring HRQoL in patients with HIV.